Governmental management of social housing as an element of state social policy: Bibliometric analysis - Mammadova, Fidan; Fatakhova , Nargiz; Mammadov, Shaban; Gasimov, Ruslan; Aliyev, Shukur (LLC CPC Business Perspectives, 2024)
Social housing for socially vulnerable segments of the population is a significant component of governmental social policy, as it is directly linked to demographic and migration processes, socially vulnerable groups and people with special needs, poverty alleviation, social integration, and community development. The study conducts a bibliometric analysis (using VOSviewer tools) of the scientific literature on social housing policy and management. The study filtered more than 6,000 research papers indexed in the Scopus database from 1983 to 2024. The purpose was to structure the global scientific knowledge on governmental management of social housing as an element of the state’s social policy, focusing on the following directions. The first is the evolution of scientific thought. The analysis revealed a rapid growth in scientific interest starting from 1991; the earliest articles were published in the United Kingdom, Netherlands, and the United States, while scholars from Spain, Mexico, and Italy joined after 2020. The second is the complexity or conversely – concentration of research networks. The top five countries by the number of works are the United Kingdom, Australia, the Netherlands, Italy, and the United States; the most powerful research schools are in the Netherlands, Australia, and the United Kingdom; the most extensive scientific connections are held by the Netherlands, the United States, the United Kingdom, Italy, and France. The third is the content-thematic orientation of the research. The paper identified the predominance of works from social sciences; social housing issues are most frequently studied in connection with public health and inequality issues.